Estudo dos parâmetros de soldagem do eletrodo kst eh cr 70 contra o desgaste abrasivo - Pitoli, Ana Carolina Goulart (2024)
This dissertation presents an experimental analysis of the behavior of the KST EH CR 70 electrode under abrasive wear, aiming at its application in the repair of components used in the sugar and alcohol industry, specifically in sugarcane chopper knives. The study begins by highlighting the economic and energy relevance of the sector in Brazil, the world's largest sugarcane producer, whose productivity is affected by the severe wear of operational parts due to contact with impurities such as sand, stones, and metals. To address this issue, hardfacing welding is applied to extend the service life of components. The research seeks to investigate the optimal parameters for applying the KST EH CR 70 electrode through shielded metal arc welding, combined with buttering using the E7018 electrode to improve the metallurgical bonding and quality of the coating layer. The methodology includes the preparation of test specimens, application of coatings using different parameters, tribological tests using a rubber wheel, Vickers microhardness tests, and microstructural analysis using optical microscopy. The results show variations in wear resistance and hardness depending on the combination of parameters, allowing the identification of those that offer the best performance, with lower mass loss, greater surface integrity, and more stable behavior under friction. It is also observed that the KST EH CR 70 electrode, when properly applied, demonstrates good abrasion resistance, proving effective in the repair of worn parts in the sugar-energy industry. The complementary numerical analysis reinforces the experimental data, demonstrating consistency between simulation and physical test results. The study contributes to the optimization of corrective and preventive maintenance processes in industrial plants by proposing high-performance coating alternatives, with a direct impact on reducing operational costs, increasing equipment lifespan, and improving efficiency in sugarcane processing. It is concluded that the controlled application of the KST EH CR 70 electrode in welding processes can represent a technically viable and economically advantageous solution for the sector, provided that proper substrate preparation, thermal parameters, and weld bead quality are ensured